Pacific Symposium on Biocomputing 2006 : Hawaii, USA, 3-7 January 2006 - Pacific Symposium on Biocomputing (2006 : Maui, Hawaii); Altman, Russ B. (Singapore : World Scientific Publishing Company, 2006)
42